Cold treachery - Todd, Charles (New York : Bantam Books, 2005)
Called out into the teeth of a violent blizzard, Inspector Ian Rutledge faces one of the most savage murders he$1 (Bs ever encountered. He might have expected such unspeakable carnage on the World War I battlefields where he$1 (Bd lost much of his soul$1 (Band his sanity$1 (Bbut not in an otherwise peaceful farm kitchen in remote Urskdale. Someone has murdered the Elcott family without the least sign of struggle. But when the victims are tallied, the local police are in for another shock: One child is missing. Now the Inspector must race to save a young boy before he$1 (Bs silenced by the merciless elements$1 (Bor the even colder hands of the killer who hides in the blinding snow. s
Reprint. Originally published in hardcover, 2005.
91667
Keywords: Rutledge, Ian (Fictitious character); Mass murder investigation; Police -- England; Missing children; Child witnesses; England, Northern; Historical fiction; Mystery fiction